Profile of specific and associated autoantibodies in patients with idiopathic inflammatory myopathies in a Colombian population - Hormaza-Jaramillo, Andrés; Bedoya-Joaqui, Vanessa; Puerta-Sarmiento, Germán; Bautista, Mario; Rios-Serna, Lady J.; Delgado-Mora, Tatiana; Nieto-Aristizábal, Ivana; Ruiz-Ordoñez, Ingrid (Frontiers in Medicine, 2022)
Objectives: Idiopathic inflammatory myopathies (IIMs) are chronic, autoimmune diseases with several forms of presentation. Diagnosis is mostly clinical in our region. Our aim was to evaluate the autoantibody profile of patients with IIMs. Methods: This study is a cross-sectional study with a prospective recollection of data, conducted between 2019-2021, in a single center in Cali, Colombia. Patients with a clinical diagnosis or suspicion of IIM were included. The presence of myositis-specific/associated antibodies was evaluated by immunoblotting in serum samples. Phenotypic characterization was performed. Results: A total of 36 patients were included. The mean age was 50.6 (16.7) years, and 20 (55.6%) were female. Eighteen (50%) patients were seropositive, of which 11 (30.5%) presented one positive antibody, with anti-TIF1ɣ being the most frequent (n=4, 11.1%), followed by anti-Ro52 (n=2, 5.6%). Seven patients (19.4%) showed >1 positive antibody. Dermatomyositis was the most frequent type of IIM in seropositive patients (n=8, 44.4%), followed by anti-synthetase syndrome (n=3, 16.7%). Weakness was symmetric and presented in the upper and lower extremities in 11 (61.1%) patients each. Both respiratory insufficiency and weight loss were seen in 7 (38.9%) patients, Gottron papules in six (33.3%) patients, and heliotrope rash, esophageal dysmotility, and myalgia in 5 (27.8%) patients. Pulmonary interstitial disease was seen in 4 (22.2%, with antibodies for anti-Ro52, anti-MDA5 + anti-Jo1 + anti-TIF1ɣ, anti-MDA5 + anti-SAE1 + anti-NXP2, and anti-cN1A + anti-Ro52) patients, and malignancy was seen in 2 (11.1%) patients (1 with anti-Mi2β and 1 with anti-TIF1ɣ + anti-Mi2α). In all, 7 (19.4%) patients required intensive care (2 seropositive, 1 with anti-PL7, 1 with anti-MDA5 + anti-Jo1 + anti-TIF1ɣ), and 1 (2.8%) (seronegative) patient died. Conclusions: This study is the first study in Colombia that evaluates myositis-specific/associated antibodies in IIM. Half of the patients were seropositive according to the literature. Several patients presented antibody combinations. Further studies are needed to fully associate phenotypes with antibodies.